Virtual reality simulation of human-robot coexistence for an aircraft final assembly line: process evaluation and ergonomics assessment. Issue 9 (2nd September 2021) - Ottogalli, Kiara; Rosquete, Daniel; Rojo, Javier; Amundarain, Aiert; María Rodríguez, José; Borro, Diego
ABSTRACT: Aeronautics, in the context of industry 4.0, is continuously evolving to respond to the market dynamics and has incorporated automation to many stages of aircraft manufacturing. However, most of the final assembly line processes are still done manually and remain a challenge. Virtual Reality (VR) technologies can be leveraged to study the incorporation of automation systems involving Human-Robot Coexistence (HRC) in assembly processes before the physical system is available, which is beneficial for increasing the productivity and identifying issues beforehand, thus, preventing unexpected costs. In this context, a VR simulation environment was developed with two innovative factors: (1) The possibility to evaluate multiple new automated and semi-automated cabin and cargo processes and select the best one in terms of specific Key Performance Indicators (KPIs) for a future implementation in the physical system and (2) the capability to study the ergonomics of the human worker inside the narrow space of the fuselage while assembling the parts and coexisting with robots, without compromising the worker's safety. The results show that most of the new proposed strategies improve the assembly time, worker cost, or ergonomics of the process, with an investment varying between 100 K and 200 K euros and ROI of 1–2 years.